Nursing Theory Application of Need for Help Wiedenbach and Social Support in Pregnant Women with Incomplete Abortion - Bestfy Anitasari (Institute of Computer Science (IOCS), 2020)
The research purpose to apply Wiedenbach's Need For Help and Social Support Theory in incomplete abortion nursing care. This research method was a descriptive study to describe the application of nursing theory in cases of incomplete abortion. The results of this research explain that the theory of need for help is suitable for use in acute conditions of incomplete abortion patients due to abdominal pain and bleeding, while the social support theory is used in fulfilling the psychological intervention of patients because of the anxiety or fear they experience. The conclusion of this study that the use of social support theory can improve the provision of nursing care by applying the theory of need for help to clients with incomplete abortion.